Effect of Dimensionless Hydrodynamic Parameters on Coarse Particles Flotation - SHAHBAZI, B.; REZAI, B.; JAVAD KOLEINI, S.M. (Asian Journal of Chemistry, 2010)
The upper particle size is an important parameter in flotation operation and the sharp decrease of flotation response when particle size approaches such a limit is well known phenomenon. Nowadays, particle size is often measured and controlled in flotation concentrators. In this study the dependence of the dimensionless hydrodynamic parameters (Reynolds Number-Re, Froude Number-Fr and Weber Number- We) on the particle size variation was investigated on the quartz particles using laboratory mechanical flotation cell. Maximum flotation response was observed at Re = 89800, Fr = 2.4 and We = 1558. For either more quiescent (Re < 73500 and Fr < 1.61) or more turbulent (Re > 106200 and Fr > 3.35) conditions, flotation recovery decreased steadily. Under more quiescent hydrodynamic conditions, the lower recovery was due to the fact that the impeller was not capable of keeping particles in suspension properly whereas under more turbulent conditions the disruption of particle/bubble aggregate was intensively observed. Furthermore, amount of collision probabilities is calculated using various equations. According to this study, with increasing particle size or impeller velocity, increase in probability of collision and with increasing air flow rate, decrease in probability of collision was observed.